KAJIAN DAN PEMODELAN RUMAH SEDERHANA BERDASARKAN PRIVASI DI KOMUNITAS BERPAGAR (GATED COMMUNITY) - Hia, Osismat; Rahmawati, Anna Lucy; Silitonga, Shanty (Unika Santo Thomas, 2018)
Privacy is essential for individual or community because it is aimed at providing a feeling of independence, giving an opportunity to release emotions, help self-evaluate, limit and protect yourself from communication with people. Housing in the gated community is now found to be built solely to be a place to live forgot the privacy. Most of the resident of houses in the gated community are people coming from different regions with different cultures. It is essential to provide the right model for a simple home that can bring about the privacy to residents. This study was categorized into a study using simulation and modeling research strategies. Simulation and modeling research strategy is a form of research using an artificial model of a particular process or system that will be tested through a simulation process, both natural phenomena and man-made phenomena. The phenomenon can be the form, activity, characteristics, changes, relationships, similarities and differences between one phenomenon with other phenomena. The benefit of this research is to find the right home design model based on the privacy of the occupants in a simple house, any elements of the house that can influence it and find a model that can be applied to simple home design in general.